Екуменізм та релігійна нетерпимість - Стаднік, Д. В. (ХНУРЕ, 2020)
The purpose of the article is philosophical understanding the problem of ecumenism and religious intolerance. The main advantages and disadvantages of modern religions are listed there. The themes of religious intolerance and the persecution of dissidents are given consideration. The question about the harms or benefits of global religion remains debatable.
Keywords: філософія; релігійна нетерпимість